2014
DOI: 10.1002/elps.201400224
|View full text |Cite
|
Sign up to set email alerts
|

Chiral analysis of amino acid neurotransmitters and neuromodulators in mouse brain by CE‐LIF

Abstract: Chiral CE method has been developed for quantitative determination of d-amino acid modulators of NMDA glutamate receptor; d-serine and d-aspartate along with l-glutamate and l-aspartate in biological samples. These ligands are suggested to be involved in regulation of NMDA receptor related brain functions, such as neurogenesis, neuronal plasticity, and memory formation. For sensitive determination of the amino acids LIF detection was chosen, and a fluorogenic reagent, 7-fluoro-4-nitro-2,1,3-benzoxadiazole was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…LIF is the detection system which offers the best sensitivity of all the detectors used in CE and an evidence of this is the low LODs depicted in Table , generally in the nanomolar range even though the reported works did not employ additional preconcentration strategies . Moreover, in a recent published review article, it was demonstrated that LIF has been the most employed detector system in CE to determine chiral neuroactive molecules (e.g.…”
Section: Strategies To Enhance the Detection Sensitivitymentioning
confidence: 99%
“…LIF is the detection system which offers the best sensitivity of all the detectors used in CE and an evidence of this is the low LODs depicted in Table , generally in the nanomolar range even though the reported works did not employ additional preconcentration strategies . Moreover, in a recent published review article, it was demonstrated that LIF has been the most employed detector system in CE to determine chiral neuroactive molecules (e.g.…”
Section: Strategies To Enhance the Detection Sensitivitymentioning
confidence: 99%
“…CE laser induced fluorescence (LIF) detection systems are increasingly used for the chiral separation of all the amino acids due to the high separation efficiency, and compatibility with sensitive detection methods including MS instruments [43]. Although the LOD by such method achieves concentration of the low nM for several molecules [44], recent data related to d -Asp quantification showed LOD of 17 nM (2.3 ppb) in chicks brain tissues [45] and 8 nM (1 ppb) in various brain regions of adult mice [46], 4 and 2 fold, respectively, higher than LOD recorded with our MRM method. Peak assignments for most of these methods needed to be confirmed [47].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitive determination of amino-acid neurotransmitters and neuromodulators in mouse brain was achieved by CE-LIF using 7-fluoro-4-nitro-2,1,3-benzoxadiazole for derivatization and HPrAMCD as chiral selector [35]. The limit of quantification (LOQ) was obtained an accuracy of 0.05 µM for D-serine and D-aspartate.…”
Section: Monocationic and Dual-cationic Cds As Chiral Additivesmentioning
confidence: 99%